Unveiling Legends: A Journey through Cultural Folklore - Teixeira, Denise Q. M.; Moraes, João Victor L. de; Camara, Davi R. de O.; Abbud, Gabriel C. da Silva; Oliveira, Thiago Narak C. de; Rodrigues, Maria Andréia F. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This paper presents “Caturama,” a serious game prototype crafted for educators, students and proponents of cultural heritage preservation. Designed to immerse players in the rich folklore of the Brazilian Amazon’s indigenous tribes, its conception was guided by twin goals: authenticity in visual and narrative representation and engaging user experience. Drawing inspiration from three iconic legends of the region, Caturama seeks to bridge the gap between the modern world and ancient traditions. Detailed within are the design principles, developmental methodologies, and user feedback analytics. With a favourable Net Promoter Score of +70, it underscores the game’s appeal and its potential as an educational medium for fostering cultural understanding and preservation.